Laboratory stand for development of method and system for continuous non-contact non-destructive testing of technical condition of insulation equipment - T. G. Galieva; D. A. Ivanov; M. F. Sadykov; A. V. Golenishchev-Kutuzov (Омский научный вестник)
Measurement of partial discharges (PD) is a generally accepted method of diagnosing the insulation of electrical equipment worldwide. Today, the trend is to move from conventional offline testing to online monitoring to predict the service life of insulation. For testing and calibration of the developed new methods with the contact method, a laboratory stand has been developed in accordance with GOST R 55191-2012 (IEC 60270:2000). The article suggests the use of acoustic and electromagnetic methods for a system of continuous non-contact non-destructive testing of the technical condition of insulation equipment, which will allow monitoring insulation equipment online and predicting its residual life. On their basis, a system of «on-line» diagnostics of high-voltage insulators has been developed.